Mengembangkan Platform HEAL-U: Peningkatan Layanan Konseling Online Untuk Kesejahteraan Pengguna - Muhammad Rio Sahri Syawal; Sri Irmayani; Athiyyah Anandira; Sumarno (Sakura Digital Nusantara, 2024)
Adolescence is a crucial transitional phase between childhood and adulthood, marked by significant emotional changes. Teenagers often struggle to adapt to these changes, which can lead to serious issues such as depression and anxiety. According to data from the Basic Health Research, approximately 6.1% of the Indonesian population experiences emotional mental disorders. To address this issue, the Heal-U platform was developed, an online counseling system designed to provide mental support for teenagers. The development method used is the waterfall model, starting from planning to system implementation and testing. Testing was conducted using both black-box and white-box approaches to ensure the system's functionality and reliability. The results show that Heal-U can be effectively implemented and has great potential to reduce the rates of depression and suicide among teenagers.